Targeting the safe zone: A quality improvement project to reduce vascular access complications. Issue 1 (15th March 2017) - Mignatti, Andrea; Friedmann, Patricia; Slovut, David Paul
Abstract : Objective: The aim of this study was to assess the effectiveness of a quality improvement (QI) program in reducing vascular complications during cardiac catheterization. Background: Vascular access complications during cardiac catheterization are associated with higher morbidity and mortality. We implemented a QI program focused on using micropuncture techniques and targeting the "safe zone, " an area below the inferior border of the inferior epigastric artery and above the inferior border of the femoral head, for femoral artery puncture. Methods: Our catheterization laboratory implemented a protocol that required all operators to use micro puncture technique during diagnostic and/or percutaneous coronary interventions and to document arteriotomy in the "safe zone." We also encouraged use of vascular ultrasound, radial artery approach, and increased use of vascular closure devices (VCDS). We analyzed data on 3120 patients (2013, pre‐QI cohort) and 3222 patients (2014, QI cohort). Data on vascular complications were prospectively collected and compared with the rate of complications that occurred during the same time one year prior when the QI project was not in effect. Results: Baseline characteristics of two cohorts of patients were similar. Compliance with the protocol was excellent. Appropriate documentation of the wire exiting the needle was observed in 95% of cases. VCD use increased from 35% in 2013 to 60% in 2014 ( P  < 0.001) There were no significant differences in the overall number of complications after implementation of the QI project (1.03% complications before QI implementation and 0.96% after QI implementation. P  = 0.79) but there was an absolute reduction in the number of hematomas (0.77 vs. 0.40% in 2013 vs. 2014, respectively, P  = 0.06) and of pseudoaneurysms (0.35 vs. 0.19% P  = 0.20). Correlates of major vascular complications included), age > 75 years (HR 3.1, P  < 0.0001), and PCI (vs. diagnostic cath). Conclusions: Micropuncture technique in association with "safe zone targeting "did not significantly reduce vascular complications in patients undergoing cardiac catheterization, but a trend toward decrease of hematomas and pseudoaneurysms was noted. Factors such as age and type of procedure (PCI vs. diagnostic) play a significant role in the occurrence of vascular complications. © 2017 Wiley Periodicals, Inc.